2016
DOI: 10.1186/s12936-016-1516-y
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil gelatinase-associated lipocalin (NGAL) predicts the occurrence of malaria-induced acute kidney injury

Abstract: BackgroundAcute kidney injury (AKI) is a frequently encountered complication of imported Plasmodium falciparum infection. Markers of structural kidney damage have been found to detect AKI earlier than serum creatinine-based prediction models but have not yet been evaluated in imported malaria. This pilot study aims to explore the predictive performance of neutrophil gelatinase-associated lipocalin (NGAL) and kidney injury molecule-1 (KIM-1) for AKI in travellers with imported P. falciparum infection.MethodsThi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 40 publications
1
17
0
3
Order By: Relevance
“…Patients in this study were younger (50 ± 11 years) than the patients in the previous report (77 or 87 years) . Using 0.71 as the cutoff value for predicting AKI is close to several other studies, such as septic shock, hip fracture, and major orthopedic surgery . Other researchers have reported the optimal cutoff as being 0.73 for RRI to predict persistent AKI …”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…Patients in this study were younger (50 ± 11 years) than the patients in the previous report (77 or 87 years) . Using 0.71 as the cutoff value for predicting AKI is close to several other studies, such as septic shock, hip fracture, and major orthopedic surgery . Other researchers have reported the optimal cutoff as being 0.73 for RRI to predict persistent AKI …”
Section: Resultssupporting
confidence: 78%
“…Moreover, AKI may be present in person with normal urine output . New biomarkers for earlier detection of AKI with more sensitivity was urgently needed in the postoperative management of AKI parents . Renal resistive index (RRI) was an early predictor of AKI and has been studied in several clinical situations .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…AKI is a known complication of malaria and can occur in around 40% of patients with severe disease by P. falciparum in endemic regions, contributing to high mortality rate, around 75% of cases 12 , 17 , 18 . P. falciparum causes the most severe form of malaria and is responsible for most cases of AKI 16 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has found evidence that 31% of patients with malaria-associated AKI had normal levels of creatinine at presentation, illustrating the importance of new AKI biomarkers. NGAL seems to be a good biomarker for malaria-associated AKI and has already been investigated in different types of kidney injury 18 .…”
Section: Introductionmentioning
confidence: 99%